Effective extraction of tylosin and spiramycin from fermentation broth using thermo‐responsive ethylene oxide/propylene oxide aqueous two‐phase systems. Issue 2 (16th December 2021) - Yang, Ting; Zheng, Ting; Wang, Yan; Zhang, Yan; He, Dong; Zeng, Hainan; Wei, Yanli; Chen, Xi; Wan, Junfen; Cao, Xuejun
Abstract: Recyclable aqueous two‐phase systems with thermo‐responsive phase‐forming materials have been employed to separate macromolecules; however, these systems have achieved very limited separation efficiency for small molecules, such as antibiotics. In this study, aqueous two‐phase systems composed of the ethylene oxide/propylene oxide copolymer and water were developed to extract alkaline antibiotics from the fermentation broth. In the aqueous two‐phase systems with an ethylene oxide ratio of 20 and propylene oxide ratio of 80, the partition coefficients of tylosin and spiramycin reached 16.87 and 20.39, respectively, while the extraction recoveries were 70.67 and 86.70%, respectively. Coupled with mechanism analysis, we demonstrated the feasibility of extracting alkaline antibiotics using this aqueous two‐phase system, especially for 16‐membered macrolide antibiotics. The molecular dynamic simulation was employed to visualize the process of dual‐phase formation and the partition behavior of antibiotics in an aqueous two‐phase system. The dynamic simulation revealed the binding energy between the antibiotic and ethylene oxide/propylene oxide copolymers, which provides a simple indicator for screening suitable antibiotics in aqueous two‐phase systems. Our recyclable aqueous two‐phase systems provide a robust approach for the extraction of 16‐membered macrolide antibiotics with ease of operation and high recovery rates, which is appropriate for large‐scale extraction in the fermentation industry.